Assisting the Poor to Work: A Biblical Interpretation - Beed, Clive S. (Christian scholar's review, 2010)
A conviction accepted broadly by contemporary Christians is that the poor should be assisted economically and socially. Despite the variety of Christian and secular assistance programs, little consensus occurs about how the poor should be helped. Cara and Clive Beed argue in this essay from three sets of biblical material (Genesis, the Mosaic Law, and Jesus’ teachings in Luke), assisted by the interpretations of biblical exegetes and commentators, toward the importance of providing paid work for the poor in the advanced economy, and for these jobs to be developed via particular organizational structures. The biblical discussion does not proceed further than Jesus’ teaching during His lifetime. The penultimate section considers how these structural features of work for the poor might be encouraged by Christians in the advanced economy, and gives examples of where this has been done.